Analysis of The Influence of Fintech on The Adoption Rate of Digital Financial Services - Olyvia Rosalia; Ahmad Junaidi (Nomico, 2025)
This study aims to analyze the influence of financial technology (fintech) on the level of adoption of digital financial services among the Indonesian population. Using a quantitative approach and the Partial Least Square Structural Equation Modeling (PLS-SEM) method, this research examines the variables of ease of use, user trust, perceived usefulness, and system security on the adoption level of fintech services. Data were collected through questionnaires distributed to 150 fintech users across various regions. The analysis results show that all four variables have a significant influence on the adoption of digital financial services, with perceived usefulness being the dominant factor. Ease of use and trust also play important roles in shaping users’ decisions, while the security aspect serves as a supporting factor influencing user retention. These findings offer insights for fintech developers and regulators to improve service quality and accelerate digital financial inclusion. This study also highlights the importance of consumer education and protection in the era of digital financial transformation.